APLIKASI PERINGKASAN DOKUMEN MENGGUNAKAN METODE MAXIMUM MARGINAL RELEVANCE (MMR) - Delvin Delvin; Desi Arisandi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
making a summary application to help readers who do not like to read long and thick news articles which take a relatively long time and can cause readers to be lazy to read the news articles. This summary application is used to summarize news articles, in making the application using ASP.Net. In this summary, the Maximum Marginal Relevance (MMR) method is used. In this study, you can use articles on the website, and do it. Articles are processed in the form of a file (single document) with a txt extension. The summary process goes through the preprocessing stage, which consists of sentence segmentation, case folding, tokenizing, filtering, stemming.